Microwave Absorbing Properties of Polycrystalline La0.67Sr0.33MnO3 - Laksanawati, Wahyu Dian; Burhendi, Feli Cianda Adrin; Kusdiwelirawan, Acep (Omega: Jurnal Fisika dan Pendidikan Fisika, 2019)
Sample \ce {La_{0.67}Sr_{0.33}MnO3} has been successfully synthesized by sol gel method shown by the results of XRD formed a single phase with rhombohedral crystal structure. The results of SEM showed particles are agglomerated yet functional groups \ce {Mn-O-Mn} has been formed based on the results of FTIR. The ability of the sample to absorb the microwaves still lower that the value of reflection loss obtained at $-26.05$ dB.